Composite plating film and plated product
Patent Information
- Application Number
- JP2023129447
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025015000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite plating film and a plated product. In particular, the present invention relates to a composite plating film and a plated product having improved seizure resistance without reducing the film hardness. [Background technology]
[0002] Composite plating films in which polytetrafluoroethylene resin (hereinafter referred to as "PTFE") is co-deposited with a plating film have been studied as a surface treatment technology with a low friction coefficient and excellent durability. Such composite plating films are used in sliding members and the like (for example, Patent Documents 1 and 2). Patent Document 1 discloses an electroless composite nickel-phosphorus alloy plating method for sliding parts such as a plunger piston for a gasoline fuel pump. The electroless composite nickel-phosphorus alloy plating method described in Patent Document 1 uses a plating solution in which fluororesin particles are dispersed in an electroless nickel-phosphorus alloy plating solution, and this plating solution contains a surfactant such as a cationic surfactant, a nonionic surfactant, or an amphoteric surfactant in order to disperse the fluororesin particles in the plating solution. Patent Document 2 discloses a composite plating film containing dispersed fluorine compound particles that can be used on the surface of an iron, which has high surface hardness, low wear, good sliding properties, and low static electricity generation. The composite plating film disclosed in Patent Document 2 uses a surfactant to uniformly disperse the fluorine compound particles in the plating solution.
[0003] The plating film contained in the composite plating film functions as the matrix. Nickel electroplating and electroless nickel-phosphorus plating, which have excellent hardness, are mainly used for plating films. On the other hand, PTFE contained in the composite plating film is a polymer material that functions as a solid lubricant, but its hardness is low and it has weaknesses in terms of wear resistance and usage characteristics under high surface pressure sliding conditions. For this reason, by using a plating film as a compositional component of a composite plating film and incorporating PTFE into the plating film, it is possible to compensate for the physical property weaknesses of PTFE. Therefore, in order to incorporate PTFE into the plating film, it is necessary to disperse the PTFE particles in the plating solution using various surfactants.
[0004] However, various surfactants used to incorporate PTFE into the plating film reduce the hardness of the matrix itself, which is the plating film, and deteriorate the abrasion resistance of the plating film. For this reason, composite plating films containing PTFE have problems with abrasion resistance, especially their durability under high surface pressure sliding conditions. Therefore, in order to improve the abrasion durability of the composite plating film, the addition of a self-lubricating material to the composite plating film has been considered, and cleavable crystals such as graphite, molybdenum disulfide, boron nitride, and mica have been used as self-lubricating materials.
[0005] Here, graphite and molybdenum disulfide have problems with their heat resistance, and boron nitride is expensive and has limited uses. On the other hand, mica is a plate-like mineral whose main component is silicic acid, and has high heat resistance. Since mica is an abundant resource, it can be obtained at low cost. From such a technical viewpoint, a plating film using swelling mica as a composite material has been proposed (for example, Patent Documents 3 and 4). Patent Document 3 discloses a composite plating in which swellable fluoromica is added as a dispersing material, and which prevents abnormal spherical deposition due to swelling of the fluoromica. The composite plating described in Patent Document 3 is produced by finely crushing swellable fluoromica in a swollen state and adding the mica fine particles before adding the swellable fluoromica as a dispersing agent to a base material such as nickel. Furthermore, Patent Document 4 discloses a composite plating that does not require a dispersion promoter and can form a highly lubricating film at low cost, and a sliding member using the same. The composite plating described in Patent Document 4 uses a nickel hypophosphite solution (Ni-P) as a base, to which swellable mica, or fluorine-based mica or fluorine-based swellable mica is added as a dispersing agent, to form a lubricating film on the surface of the sliding member.
[0006] Also, electroless nickel-phosphorus-silicon nitride composite plating has been proposed, which imparts new functionality such as wear resistance and self-lubrication to nickel-phosphorus composite plating, which has good characteristics (for example, Patent Document 5). The electroless nickel-phosphorus-silicon nitride composite plating described in Patent Document 5 is obtained by adding Si3N4 as wear-resistant particles together with mica to an electroless nickel plating bath using sodium hypophosphite as a reducing agent. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-49449 A [Patent Document 2] Japanese Patent Application Publication No. 9-149998 [Patent Document 3] Japanese Patent Application Publication No. 8-120457 [Patent Document 4] Japanese Patent Application Publication No. 7-62550 [Patent Document 5] Japanese Patent Application Publication No. 8-13152 Summary of the Invention [Problem to be solved by the invention]
[0008] However, the composite plating films described in Patent Documents 1 to 5 all contain swellable mica as a composite material, which is a solid lubricant contained in the composite plating film, and therefore have the problem that such swellable mica swells and becomes flaky in the plating solution used in the process of producing the composite plating film. That is, when a composite plating film is produced using swellable mica, the swellable mica has high uniform dispersibility in the plating solution, but the swellable mica is difficult to incorporate into the plating film, which makes it difficult to obtain a composite plating film with a high content of the self-lubricating composite material.
[0009] Furthermore, when a composite plating film is produced using swellable mica and electroless nickel plating as a plating solution, there is a problem in that the plating bath consisting of the plating solution lacks stability. The present invention has been made to solve the above-mentioned problems, and has an object to provide a composite plating film that can effectively suppress wear and seizure under sliding conditions by codepositing a considerable amount or more of a composite material that is a self-lubricating material. [Means for solving the problem]
[0010] The composite plating film according to the present invention is a plating film in which mica, a solid lubricant with excellent properties under high surface pressure and high heat resistance, is co-deposited with electroless metal plating such as electroless nickel-phosphorus plating, and can reduce the friction coefficient without decreasing the film hardness. The composite plating film according to the present invention can impart a property of being less likely to seize to the plated object.
[0011] In the present invention, non-swelling mica is used. The inventors discovered that by adding this to any electroless nickel plating solution, a mica composite plating film with a content of 2.0 to 12.0 mass % can be obtained without the need for a special surfactant, and thus completed the present invention. It was also revealed that the composite plating film thus obtained exhibits excellent anti-seizure properties in a sliding test. That is, the plating solution for composite plating film according to the present invention, which advantageously solves the above problems, is [1] A composite plating film having excellent sliding properties, characterized in that the composite plating film is formed from a plating solution for the composite plating film in which non-swelling mica is dispersed in an electroless metal plating solution. [2] The composite plating film according to [1], wherein the content of the non-swelling mica is 2.0 to 12.0 mass %. [3] The composite plating film according to [1] or [2], wherein the particle diameter of the particles constituting the non-swelling mica is 0.1 to 5.0 μm. [4] A plated product comprising the composite plating film described in [3]. Effect of the Invention
[0012] According to the present invention, by codepositing non-swelling mica, it is possible to provide a composite plating film that can effectively suppress wear and seizure under sliding conditions. Specifically, according to the present invention, it is possible to reduce the coefficient of friction and improve the sliding characteristics without decreasing the hardness of the composite plating film. Furthermore, according to the present invention, due to the properties of mica itself, which is the composite material contained in the composite plating film, it is possible to obtain a film that has excellent seizure resistance, particularly in a sliding environment with high surface pressure. Furthermore, according to the plating solution for composite plating films of the present invention, no special surfactant is required for the formation of a composite and the plating metal that serves as the matrix is not affected in its properties, so that a composite plating film can be produced using any plating solution. [Brief description of the drawings]
[0013] [Figure 1] 1 shows the results of a reciprocating sliding friction test with a stainless steel pin, comparing a phosphorus-containing electroless nickel-phosphorus plating film, a PTFE composite electroless plating film, and a mica composite plating film according to the present invention. [Diagram 2] 1 is a surface microscope image of a mica composite plating film produced in an example. [Diagram 3] 1 is a cross-sectional microscope image of a mica composite plating film produced in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the embodiments of the present invention will be described in detail. Note that the drawings are schematic and may differ from the actual ones. Furthermore, the following embodiments are merely examples of devices and methods for embodying the technical idea of the present invention, and are not intended to limit the configuration to the following. In other words, the technical idea of the present invention can be modified in various ways within the technical scope described in the claims.
[0015] [First embodiment] The composite plating film according to the first embodiment will be described. The composite plating film according to this embodiment is characterized in that it is formed from a plating solution for a composite plating film, which contains an electroless metal plating solution and non-swelling mica, and in which the non-swelling mica is dispersed in the electroless metal plating solution. Each composition component contained in the composite plating film according to this embodiment will be described below.
[0016] <Electroless metal plating solution> The composite plating film according to the present embodiment includes an electroless metal plating solution. The electroless metal plating solution constitutes a plating solution for the composite plating film and serves to disperse the non-swelling mica contained in the plating solution for the composite plating film. Specific examples of electroless metal plating solutions include electroless nickel plating solutions and electroless nickel-phosphorus plating solutions, as well as Ni-B, Ni-Co-P, and Ni-Co-PB, which are applicable to electroless nickel-based plating solutions.
[0017] The electroless metal plating solution may contain a water-soluble metal salt, a reducing agent, and an organic acid. The water-soluble metal salt contained in the electroless metal plating solution may be any salt that can be commonly used in a plating bath, such as nickel sulfate or nickel chloride.
[0018] Furthermore, hypophosphite, dimethylamine borane, etc. can be used as the reducing agent contained in the electroless metal plating solution. Organic acids contained in the electroless metal plating solution can be alkyl carboxylic acids such as acetic acid and propionic acid, hydroxy carboxylic acids such as lactic acid and malic acid, amino acids such as glycine and alanine, etc. The electroless metal plating solution can be adjusted to a pH of 4.0 to 9.0 by using sodium hydroxide, potassium hydroxide, ammonia water, etc.
[0019] The electroless metal plating solution may contain, as a stabilizer, a water-soluble lead compound, a water-soluble bismuth compound, an iodate, a bromate, a vanadate, a molybdate, a tungstate, or the like.
[0020] Furthermore, the electroless metal plating solution may contain organic sulfur compounds such as thiourea, thioglycol, and thiodiglycol as plating accelerators, and various ionic and nonionic surfactants as wettability improvers.
[0021] <Non-swelling mica> The composite plating film according to this embodiment contains non-swelling mica. That is, the mica contained in the plating solution for the composite plating film according to this embodiment is non-swelling mica. Non-swelling mica is mica that does not swell by absorbing a solvent contained in the electroless metal plating solution or a solvent contained in a non-swelling mica dispersion liquid described below.
[0022] Examples of non-swelling mica include fluorine mica (Mg3K[AlF2O(SiO3)]3), phlogopite (KMg3AlSi3O 10 (OH)2), Muscovite (KAl2AlSi3O 10 (OH)2), potassium fluortetrasilicic mica (KMg 2.5 (SiO 10 Here, the non-swelling mica has a layered structure, and the interlayer ions present between the layers are metal cations, such as potassium (K +Whether a mica is a swelling mica or a non-swelling mica is determined by the type of interlayer ions present between the layers constituting the mica.
[0023] That is, by appropriately selecting metal ions, it is possible to prepare the non-swelling mica contained in the composite plating film according to this embodiment. The metal ions as interlayer ions can be appropriately selected depending on the type of layer constituting the mica and the thickness of the layer, and may be cations of typical metals, cations of transition metals, or cations of rare earth metals. Various techniques for producing swellable mica or non-swellable mica by arbitrarily selecting the type of interlayer ion have been disclosed (for example, JP-A-2-149415). For example, when the interlayer ion is Li + or Na + This results in swelling mica, and K + This results in a non-swelling mica.
[0024] The content of non-swelling mica in the composite plating film according to this embodiment is preferably 2.0 to 12.0 mass %. If the content of non-swelling mica is 3.0 g / L or more, the workability of the plating solution can be improved and the friction coefficient of the plating film can be significantly reduced, which is preferable. If the content of non-swelling mica is 100g / L or less, the stirring load of the plating solution becomes large, which is preferable because it does not hinder plating workability. By setting the range of the content of non-swelling mica in this way, the content of non-swelling mica contained in the composite plating film can be set to 2.0 to 12.0 mass%. The particle diameter of the particles constituting the non-swelling mica is preferably 0.1 to 5.0 μm. If the particle diameter of the particles constituting the non-swelling mica is 0.1 μm or more, it is preferable because a plating solution for a composite plating film with a high content of non-swelling mica can be obtained. If the particle diameter of the particles constituting the non-swelling mica is 5.0 μm or less, it is preferable because the non-swelling mica is easily taken in.
[0025] The non-swelling mica contained in the composite plating film according to the present invention may be a swellable mica that has been surface-treated. The non-swelling mica may be surface-treated to provide sufficient non-swelling properties. Representative examples of the surface treatment include silane coupling treatment and oxide coating.
[0026] Examples of silane coupling agents suitable for surface treatment of the surface of swellable mica include aminopropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyldimethoxymethylsilane, etc. In this way, the silane coupling agent silane-couples the hydroxyl groups present on the surface of the swellable mica, forming an organic layer with a suitable degree of hydrophobicity on the surface of the swellable mica, which makes it easier to incorporate into the plating film.
[0027] In addition, non-swelling mica (mainly fluorophlogopite) with a titanium oxide or iron oxide coating on its surface is known as pearl mica, and is used as a pigment in paints. Non-swelling mica that has been subjected to such surface treatment can also be dispersed in a plating solution to obtain a composite plating solution, and a composite plating film can be obtained from the composite plating solution.
[0028] When adding non-swelling mica to a plating solution, it is acceptable to use the non-swelling mica in the form of a powder made up of particles constituting the non-swelling mica, but it is preferable to disperse the non-swelling mica in a solvent such as water to make it easier to handle, and to handle it as a non-swelling mica dispersion. The non-swelling mica dispersion preferably has a non-swelling mica concentration of 50 to 400 g / L, more preferably 100 to 200 g / L. If the concentration of the non-swelling mica dispersion is 400 g / L or less, it is preferable because a non-swelling mica dispersion with flowability can be prepared, and if it is 50 g / L or more, it is preferable because it is easy to handle without adding a large amount of the non-swelling mica dispersion to the plating solution.
[0029] Furthermore, a cationic polymer surfactant may be added to the non-swelling mica dispersion in order to improve the dispersion stability of the non-swelling mica. Examples of cationic polymer surfactants include Unisense FPV1000L, Unisense FCA1000L (Senka Corporation), Leoguard GP, and Leoguard MGP (Lion Specialty Chemicals Corporation).
[0030] The plating solution for composite plating film according to the present embodiment is prepared by dispersing non-swelling mica in an electroless metal plating solution. The conditions for dispersing non-swelling mica in an electroless metal plating solution are not particularly limited, but it is preferable to disperse the non-swelling mica in a predetermined amount by, for example, adding a predetermined amount of powdered mica or the mica dispersion while thoroughly stirring the plating solution with a stirrer.
[0031] [Second embodiment] A plated product according to a second embodiment will be described. The plated product according to this embodiment is characterized by having a composite plating film formed using a plating solution for a composite plating film, which contains an electroless metal plating solution and non-swelling mica, and in which the non-swelling mica is dispersed in the electroless metal plating solution. Each member of the plated product according to this embodiment will be described below.
[0032] The plated product according to this embodiment includes a composite plating film formed on a base material, that is, an object to be plated, using the plating solution for forming a composite plating film according to the above embodiment. The composite plating film provided on the plated product according to the present embodiment can be obtained by heating the plating solution for composite plating film prepared as described above to 60 to 90°C, and then immersing the plated object that has been subjected to an appropriate pretreatment in the plating solution for composite plating film, which is a mica-dispersed electroless plating solution. The film thickness of the mica composite electroless plating film can be appropriately set according to the form of the sliding member on which the film is formed, and is not particularly limited, and is, for example, 10 to 50 μm for sliding members. The mica composite electroless plating film is a composite plating film. The plated object provided with the composite plating film becomes a plated product. The plated object may be any object that can be electrolessly plated as a matrix, and the pretreatment may be similar to the electroless plating treatment. Specific examples of the object to be plated include a sliding bearing, an actuator slider, and a screw shaft.
[0033] The composite plating film thus obtained contains 2.0 to 12.0 mass % of non-swelling mica, and therefore has a low coefficient of friction and can exhibit excellent seizure resistance. EXAMPLES
[0034] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0035] <Examples 1 to 4> 1) Preparation of plating solution The chemicals shown below were dissolved in pure water to prepare an electroless plating solution. [Composition of electroless plating solution] Nickel sulfate 0.1mol / L Sodium hypophosphite 0.3 mol / L Sodium lactate 0.11 mol / L Sodium malate 0.15mol / L Bisalt 0.003mmol / L Sodium molybdate 0.4mmol / L Plating solution pH 5.0 Temperature: 85℃ (stirrer stirring)
[0036] 2) Plating test A specified amount of mica particles was added to the electroless plating solution shown in 1), and the particles were thoroughly stirred and dispersed to conduct plating experiments. An iron Hull Cell cathode plate (B-60-P01A, Yamamoto Plating Tester Co., Ltd.) was used as the substrate, and after degreasing with a steel degreasing solution (Nickel Boomer HCR Prople V, Nippon Kagaku Sangyo Co., Ltd.), it was activated by immersion in 5% hydrochloric acid, and then immersed in a plating solution heated to 85°C for 20 minutes to form a plating film.
[0037] 3) Evaluation of plating film The mica content in the film was measured using an X-ray fluorescence analyzer (Rigaku, ZSX100e), the film hardness was measured using a micro Vickers hardness tester (Mitutoyo, HM-200), and the friction coefficient and limit PV value of the film were measured using a friction and wear tester (Trinity Lab, TL-201Tt).
[0038] The friction coefficient of the plating film was measured using a stainless steel wire with a diameter of 0.45 mm as a pin and test pieces that had been subjected to various plating treatments as specimens in a reciprocating friction and wear test at a sliding speed of 100 mm / sec and a reciprocating width of 10 mm.
[0039] In Examples 1 to 4, non-swelling mica (potassium-type tetrasilicic fluoride mica) having a particle size of 0.5 to 3.0 μm was used, and plating was performed by changing the amount added to the plating solution. The particle size of the non-swelling mica used in Example 1 was set to 1.5 μm, the particle size of the non-swelling mica used in Example 2 was set to 1.5 μm, and the particle size of the non-swelling mica used in Example 3 was set to 1.5 μm, and the amounts added were changed. The particle size of the non-swelling mica was the average particle size measured by dispersing the non-swelling mica in pure water and measuring it by dynamic light scattering, and the measuring device used was an "ELSZ-2000" product manufactured by Otsuka Electronics.
[0040] <Comparative Examples 1 to 5> In Comparative Examples 1 and 2, non-swelling mica with particle sizes of 1 to 10 μm and 1 to 5 μm, respectively, was used to compare the effect of particle size. In Comparative Examples 3 to 5, a swelling layered mineral (montmorillonite: (Na, Ca) 0.33 (Al,Mg)2Si4O 10 (OH)2·nH2O) was used to compare the effect of particle swelling. The non-swelling mica used in Comparative Example 1 had an average particle size of 5 μm (distribution: 1 to 10 μm), and the non-swelling mica used in Comparative Example 2 had an average particle size of 3 μm (distribution: 1 to 5 μm).
[0041] A plating solution for a composite plating film was prepared by adding three types of non-swelling mica with different particle sizes at a concentration of 5 g / L, as shown in Table 1. The relationship between the particle size of the non-swelling mica contained in the plating solution for a composite plating film and the non-swelling mica content in the composite plating film is shown.
[0042] As is clear from Table 1, the smaller the particle size of the non-swelling mica, the greater the amount of it incorporated into the composite plating film. In addition, in the plating solution for composite plating film produced in Comparative Example 1, creamy foam formed on the plating solution surface when the amount of mica added was around 15 g / L, making it difficult to increase the amount of non-swelling mica added. Therefore, in order to obtain a plating solution for composite plating film with a high content of non-swelling mica, it is preferable that the particle size of the non-swelling mica is 5 μm or less.
[0043] [Table 1]
[0044] Next, Table 2 shows the relationship between the amount of non-swelling mica added to the electroless metal plating solution, the content of non-swelling mica in the composite plating film, and the film hardness of the composite plating film for the plating solutions obtained in Examples 1 to 4 and Comparative Examples 3 to 5.
[0045] When non-swelling mica is added, 2-5 wt% of the mica is incorporated into the film when 5-15 g / L is added, and 5-11 wt% when 30-50 g / L is added. On the other hand, when swelling mica particles are added at 70 g / L, only about 0.5 wt% is incorporated. By using non-swelling mica, a composite plating film with a high content of non-swelling mica particles can be obtained with a small amount of addition.
[0046] The hardness of the plating film is the same as when no mica is added, regardless of the mica content. Table 2 also shows three types of PTFE composite plating as Reference Examples 1 to 4, and it can be seen that the hardness of the plating film decreases with the amount of added PTFE, making it more susceptible to wear.
[0047] [Table 2]
[0048] Furthermore, the results of reciprocating friction tests of Example 2, Comparative Example 3, the base metal coating, and the PTFE composite coating (10 wt%) with a stainless steel pin are shown in Figure 1. The horizontal axis represents the PV value (sliding speed x surface pressure), and the vertical axis represents the static friction coefficient. In the reciprocating friction tests, the point at which the friction coefficient increased due to significant wear or seizure was determined to be the limiting PV value. In Example 2 and Comparative Example 3, the reciprocating friction tests were carried out under the following conditions: sliding speed 100 mm / sec, vertical load 10 g to 300 g, and sliding material SUS304 diameter 0.45 mm (cross section polished with #2000 abrasive paper before use).
[0049] 1, the composite plating film of Example 2 exhibits a limit PV value that is about five times higher than those of the composite plating film, the base metal film, and the PTFE composite plating film of Comparative Example 3. Thus, it was found that the composite plating film of Example 2 is a film that is less likely to seize in a high surface pressure environment.
[0050] Figure 2 shows a surface microscope image of the mica composite plating film produced in the examples. Specifically, Figure 2 shows the film surface of the mica composite plating film produced in Example 3, observed with an optical microscope. As is clear from Figure 2, when the mica composite plating film produced in Example 3 is subjected to sliding on a plated member, the film surface is slightly worn away and the mica in the film is supplied to the sliding surface, effectively reducing the friction coefficient and preventing seizure. Figure 3 shows a surface microscope image of the mica composite plating film produced in the example. Specifically, Figure 3 shows a polished cross section of the mica composite plating film produced in Example 3, observed with an optical microscope. As is clear from Figure 3, the lower part of the photograph is the material, the upper part is the embedding resin, and the center is the composite plating film. It can be seen that mica (visible as black lines in the film) is incorporated from the material surface to the plating film surface.
[0051] As described above, the present invention is a composite of an electroless nickel plating film and non-swelling mica, which is a solid lubricant, and a composite plating film is obtained from a plating solution for a composite plating film with a high mica content by using non-swelling mica. This makes it possible to obtain a composite plating film with a reduced friction coefficient without reducing the hardness of the composite plating film and with excellent sliding properties under high surface pressure.
Claims
1. A composite plating film having excellent sliding properties, characterized in that the composite plating film is formed from a plating solution for the composite plating film in which non-swelling mica is dispersed in an electroless metal plating solution.
2. 2. The composite plating film according to claim 1, characterized in that the content of the non-swelling mica is 2.0 to 12.0 mass %.
3. 3. The composite plating film according to claim 1, wherein the particle size of the particles constituting the non-swelling mica is 0.1 to 5.0 μm.
4. A plated product comprising the composite plating film according to claim 3.
Citation Information
Patent Citations
Composite plating and sliding member using the plating
JP1995062550A
Electroless nickel-phosphorus-silicon nitride composite plating bath
JP1996013152A
Composite plating and sliding member using the same
JP1996120457A
Iron
JP1997149998A
Method for plating electroless composite nickel- phosphorus alloy
JP2001049449A